Invariant probabilities for Feller-Markov chains. (1995) - Hernández-Lerma, Onésimo; Lasserre, Jean B.
Abstract : We give necessary and sufficient conditions for the existence of invariant probability measures for Markov chains that satisfy the Feller property.